2019
DOI: 10.1080/20002297.2019.1660566
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing of whole saliva from patients with primary Sjögren’s syndrome and non-Sjögren’s sicca reveals comparable salivary microbiota

Abstract: Objective:To characterize and compare the salivary microbiota in patients with pSS and patients with non-Sjögren's-related sicca, and to relate the findings to their oral health status and saliva flow rates. Methods:Twenty-four patients fulfilled the 2016 classification criteria for pSS and 34 did not (non-pSS). A clinical examination included registration of decayed, missing and filled teeth/-surfaces and collection of whole saliva. The microbiota was characterized using next-generation sequencing of the V1-V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 36 publications
2
36
2
Order By: Relevance
“…Thus, we chose to collect oral bacteria by whole mouthwash. While previous studies reported no difference or a decreased Shannon diversity in SS [10,11,13,14,17], we…”
Section: Plos Onecontrasting
confidence: 92%
See 1 more Smart Citation
“…Thus, we chose to collect oral bacteria by whole mouthwash. While previous studies reported no difference or a decreased Shannon diversity in SS [10,11,13,14,17], we…”
Section: Plos Onecontrasting
confidence: 92%
“…Dysbiosis of the oral microbiota in SS has been reported [10][11][12][13][14][15][16], but its connection to the etiopathogenesis of SS remains unclear. In addition, a recent study reported that the salivary microbiota of SS patients is comparable to that of non-SS sicca patients [17]. This study aimed to characterize the oral microbiota in SS and to investigate its potential role in the pathogenesis of SS through additional in vitro and ex vivo studies using selected bacterial species.…”
Section: Introductionmentioning
confidence: 99%
“…This cross‐sectional case‐control study included 40 consecutive patients referred to the clinic of Oral Medicine for evaluation of pSS, and who had taken part in a larger study 18 . Twenty‐four patients turned out to fulfill the classification criteria for pSS, whereas 16 patients did not (non‐pSS, randomly selected from the original non‐pSS cohort).…”
Section: Methodsmentioning
confidence: 99%
“…Details regarding the content of the clinical examination and interview have previously been described, 18 including data on general health, for example, comorbidity, medication intake, smoking habits, and symptoms of oral and ocular dryness as well clinical oral health status. Assessment of disease activity was performed using the EULAR Sjögren's syndrome Disease Activity Index (ESSDAI), which include constitutional, lymphadenopathy, glandular, articular, cutaneous, pulmonary, renal, muscular, PNS, CNS, and biological and hematological domains 19 .…”
Section: Methodsmentioning
confidence: 99%
“…Almost all of the published articles are cross-sectional studies in which it was desired to investigate the composition of the oral microbiota in order to identify one or more microorganisms to be correlated to a specific pathology. Most reports analyze the microbiota of saliva or bacterial plaque [18][19][20], but some publications, especially in the field of oncology, also evaluate the microbiota on biopsies tissues [21].…”
mentioning
confidence: 99%